Diabetic Foot Talk-Time: framework for effective communication in diabetic foot management - Cacciatore, Lavinia; Meloni, Marco (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionDiabetic foot syndrome is a prevalent and costly chronic complication of diabetes mellitus, linked to high mortality rates and significant psychological and social burdens. These challenges exacerbate the disease’s impact and can hinder the ability of healthcare professionals to effectively connect with patients. Therapeutic education and effective communication can play crucial roles in fostering patient empowerment and adherence to care, which can help reduce frustration for both patients and caregivers. However, there is currently a lack of specific guidelines to direct healthcare professionals in diabetic foot care. This study employs a mixed-methods approach, integrating a systematic literature review and a cross-sectional survey, to evaluate existing communication strategies and develop a structured digital framework aimed at improving diabetic foot care. The research focuses on reviewing recent literature (from the past five years) on effective communication and therapeutic education in the prevention and management of Diabetic Foot Syndrome. Additionally, it includes an analysis of existing manuals on communication strategies and a descriptive survey to assess professional–patient and interprofessional communication challenges, identify areas for improvement, and measure levels of awareness among diabetic patients.Materials and methodsThe literature review was conducted using the PICO method on the Medline database through PubMed, yielding 273 articles, of which eight were selected for in-depth analysis. A survey, conducted over four months, included 165 participants divided into professional and diabetic groups, each receiving targeted questionnaires.ResultsThe analysis of selected articles and communication manuals highlighted key themes aligned with the study’s objectives. Findings emphasized that self-management, effective communication, professional training in therapeutic education, and the use of information and communication technologies (ICT) are essential to improving patient adherence to diabetic foot care and optimizing therapeutic outcomes. Survey results revealed that a large proportion of diabetic patients reported either not receiving information on diabetic foot syndrome from healthcare professionals or only receiving it post-complication, leading many to seek information online. Both professionals and patients acknowledged that online resources enhance adherence to care.DiscussionThe study underscores the need for reliable, accessible resources, including multimedia support for active health education aimed at both healthcare professionals and diabetic patients at risk of foot complications. Based on these findings, a prototype framework was developed—a web platform designed to support professionals and diabetic patients with features such as daily podiatric routines, alert systems, instructional images, and practical examples to integrate into clinical practice. Additionally, the platform includes a community space for feedback and interprofessional communication. The vision is to develop a mobile application a “virtual network of connection” designed to enhance the training of healthcare professionals and improve the care of diabetics with at-risk feet. This online framework could serve as a valuable tool to motivate and guide both professionals and patients along a path of effective prevention and care. By integrating into a secure web-based health network, it aims to provide accessible, reliable resources for better management of diabetic foot health.